2005
DOI: 10.1089/end.2005.19.1203
|View full text |Cite
|
Sign up to set email alerts
|

New Bipolar Resection Device for Transurethral Resection of the Prostate: Firstex-Vivoandin-VivoEvaluation

Abstract: Our results suggest that bipolar resection offers an alternative to conventional monopolar TURP. The advantage of a more localized energy field is at least in part compensated for by the higher generator output power during the procedure. Our ex-vivo results indicate a reduced bleeding rate compared with monopolar resection. Clinical studies have to be performed to prove the significance of our findings for patient treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 20 publications
0
24
0
Order By: Relevance
“…One explanation might be that the cutting loop of the gyrus device is slightly smaller than the standard resection loop. Another attempt to explain the slower resection speed (0.44 vs. 0.56 g/min) with the bipolar method is that there is a small delay (0.8 s) [23] with each cut until the plasma corona is formed. We found two trials that also reported longer operating times with the bipolar system [9,24].…”
Section: Discussionmentioning
confidence: 99%
“…One explanation might be that the cutting loop of the gyrus device is slightly smaller than the standard resection loop. Another attempt to explain the slower resection speed (0.44 vs. 0.56 g/min) with the bipolar method is that there is a small delay (0.8 s) [23] with each cut until the plasma corona is formed. We found two trials that also reported longer operating times with the bipolar system [9,24].…”
Section: Discussionmentioning
confidence: 99%
“…Recent experimental laboratory investigations showed a lower bleeding rate and deeper coagulation capacity with the bipolar armamentarium [ 10,11 ] . This could lead to a lower blood loss, fewer transfusions and a reduced risk of clot retention in the clinical setting.…”
Section: T U E B a N D T R A N S U R E T H R A L R E S E C T I O N I mentioning
confidence: 99%
“…Wendt-Nordahl et al [11] also confirmed that the bleeding rate was lower in the Vista system (another bipolar resection device, ACMI Corporation, USA) with increasing output power (at level 7 and level 8) than monopolar TURP. Wendt-Nordahl et al [12] still reported that compared with conventional monopolar resection, bleeding was significantly reduced when tissue ablation was performed with the bipolar resectoscope (another one developed by Karl Storz, Germany). But the coagulation zones were found to be smaller [11] and marginally deeper although not statistically significant [12] ex vivo.…”
Section: Resultsmentioning
confidence: 99%
“…Wendt-Nordahl et al [12] still reported that compared with conventional monopolar resection, bleeding was significantly reduced when tissue ablation was performed with the bipolar resectoscope (another one developed by Karl Storz, Germany). But the coagulation zones were found to be smaller [11] and marginally deeper although not statistically significant [12] ex vivo. Here, the results comparing the depths of the coagulation zones with bipolar resection and monopolar TURP were divergent.…”
Section: Resultsmentioning
confidence: 99%